IMPACT OF THE COVID-19 PENDEMI ON STUDENT LEARNING IN INDONESIA - Manurung, Edison Hatoguan; Saragi, Mangaraja L; Sinaga, Sani Triwardani (Yayasan Education and Social Center, 2022)
Learning is a very important need for all students, Humans, and so does the State or Government. Learning also always has obstacles or problems for human life itself. The aims of this research are 1) to increase students' insight in distance learning (online), 2) to improve student learning mindsets, 3) to improve students' abilities in technology, 4) ways to overcome student difficulties in online learning. The problem of educational learning that is currently happening is the Covid-19 virus. Therefore, learning in Indonesia is now disrupted and in addition, face-to-face learning in schools is abolished. The government also enforces online learning for all students and other schools. The government should also improve or fulfill the existing education system in Indonesia. For example, the quota is free for students or other schools